Impaired Inhibitory Function of Presynaptic A1-Adenosine Receptors in SHR Mesenteric Arteries - Carolina Rocha-Pereira; Silvia Magdalena Arribas; Paula Fresco; Maria Carmen González; Jorge Gonçalves; Carmen Diniz (Elsevier, 2013)
In hypertension, vascular reactivity alterations have been attributed to numerous factors, including higher sympathetic innervation/adenosine. This study examined the modulation of adenosine receptors on vascular sympathetic nerves and their putative contribution to higher noradrenaline spillover in hypertension. We assessed adenosine receptors distribution in the adventitia through confocal microscopy, histomorphometry, and their regulatory function on electrically-evoked [3H]-noradrenaline overflow, using selective agonists/antagonists. We found that: i) A1-adenosine receptor agonist (CPA: 100 nM) inhibited tritium overflow to a lower extent in SHR (25% ± 3%, n = 14) compared to WKY (38% ± 3%, n = 14) mesenteric arteries; ii) A2A-adenosine receptor agonist (CGS 21680: 100 nM) induced a slight increase of tritium overflow that was similar in SHR (22% ± 8%, n = 8) and WKY (24% ± 5%, n = 8) mesenteric arteries; iii) A2B- and A3-adenosine receptors did not alter tritium overflow in either strain; iv) all adenosine receptors were present on mesenteric artery sympathetic nerves and/or some adventitial cells of both strains; and v) A1-adenosine receptor staining fractional area was lower in SHR than in WKY mesenteric arteries. We conclude that there is an impaired inhibitory function of vascular presynaptic A1-adenosine receptors in SHR, likely related to a reduced presence of these receptors on sympathetic innervation, which might lead to higher levels of noradrenaline in the synaptic cleft and contribute to hypertension in this strain. [Supplementary Figures: available only at http://dx.doi.org/10.1254/jphs.12266FP] Keywords:: adenosine receptor, mesenteric adventitia layer, confocal image, modulation, hypertension